(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The objective of this study is to determine the advisability of introducing adaptive control of the indentation made by the drilling tool depending on the structural characteristics of the processed part. In the cases when the adaptive control is economically advisable, the selection of the technological cycle and the speed of moving of the tool can be achieved by the implementation of the respective algorithm for optimization of the dimensions fed for drilling.